CHRONOLOGY OF THE MIDDLE-UPPER PLIOCENE SUCCESSION IN THE STRONGOLI AREA: CONSTRAINTS ON THE GEOLOGICAL EVOLUTION OF THE CROTONE BASIN (SOUTHERN ITALY) - Capraro L.; Consolaro C.; Fornaciari E.; Massari F.; Rio D. (My University, 2006)
The aim of this study is to reconstruct the evolution of the Strongoli area, a critical sector of the Crotone Basin (Calabria, Southern Italy), where a thick Middle-Upper Pliocene marine succession is present. The Strongoli succession shows prominent changes in the sedimentary environment that are partly forced by tectonics. Major tectonostratigraphic events have been recognized that might correlate with spreading pulses in the back-arc Tyrrhenian Sea. In particular, we demonstrate that a dramatic basinal collapse at c. 2.3 Ma correlates with the so-called 'Calabrian transgression' Auctorum and is close in age to the oceanization of the Marsili Basin. © The Geological Society of London 2006.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен